Chronicling the chronicler : the Book of Chronicles and early second temple historiography - Evans, Paul S.; Williams, Tyler F. (Eisenbrauns, 2013)
The thirteen essays in this volume are largely revised papers which were originally presented as part of the Ancient Historiography Seminar of the Canadian Society of Biblical Studies and they investigate particular texts of Chronicles, examine central themes, and consider future prospects for Chronicles study. The volume includes chapters by Shannon E. Baines, Ehud Ben Zvi, Mark J. Boda, Keith Bodner, Paul S. Evans, Louis Jonker, Gary N. Knoppers, Christine Mitchell, Peter J. Sabo, Steven J. Schweitzer, and John W. Wright. The essays represent many different perspectives, methodologies, and conclusions regarding the Chronicler's work and this volume will be of particular interest to scholars and students of Chronicles, ancient Israelite historiography and biblical literature in general.